THU0460 Tenascin-C in Joint Regeneration After Induced Osteoarthritis in the Newt Notophthalmus Viridescens. (9th June 2015) - Schoenfeld, C.; Susanto, S.A.; Geyer, M.; Schreiyäck, C.; Lange, U.; Looso, M.; Braun, T.; Neumann, E.; Müller-Ladner, U.
Abstract : Background: In mammals tissue destruction often results in fibrotic scar tissue formation, which significantly impairs organ function. In contrast, many urodele amphibians have a remarkable regenerative capacity: Damaged tissues or even lost extremities are almost perfectly regenerated, both in function and size. We established the red-spotted newt Notophthalmus viridescens as a model organism to study endogenous knee joint regeneration in adult vertebrates. In this model, osteoarthritis (OA)-like symptoms can be induced by intra-articular injection of collagenase or surgical removal of articular cartilage. Treated animals primarily display joint instability and luxation, but joint functionality is completely restored after approximately 3 months. Objectives: To identify key players involved in the underlying mechanisms driving knee joint regeneration using a high resolution gene analysis approach. Methods: A cDNA array was performed after surgically and collagenase-induced knee damage in newts, and dysregulated candidate genes were selected. Microarray results were verified on the mRNA level by real-time PCR. Protein expression levels of the dysregulated candidates were analysed by immunohistochemistry (IHC). Additionally, in vitro experiments in newt-derived cell lines and primary newt cells (chondrocytes/fibroblasts) with tenascin-C (TN-C) knockdown were performed. Results: Several matricellular proteins including TN-C were found to be upregulated during the regenerative process (at day 10 TN-C vs. control 22.4-fold in collagenase-induced OA model, 15.6-fold in surgically induced OA model). IHC revealed high TN-C expression in the periosteum in untreated newt legs. During the early phase of regeneration (at day 10) additional expression at the injury site (surgically induced OA) was observed. At later stages (20 and 40 days after injury) TN-C expression was detectable in regenerating tissues including articular cartilage. In adhesion experiments using the newt-derived cell line B1H1 TN-C coating had anti-adhesive properties (TN-C vs. control: 42% reduction). However, TN-C knock-down in newt cell lines and primary newt cells did not alter cellular adhesive behaviour. Conclusions: TN-C plays an important role during knee joint regeneration. Further detailed studies will facilitate to identify additional molecular pathways guiding these regenerative processes unique for the newt and might allow the transfer to the development of new treatment options for human OA. Disclosure of Interest: None declared